2014
DOI: 10.3109/09687637.2014.899990
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the Alcohol norms literature: A focus on context

Abstract: Objective: To proffer a theoretically driven assess ment of the validity of research which examines alcohol-related normative beliefs. Methods: A systematic review of 68 articles match ing the inclusion criteria, published between 1970 and 2013. Results: Potential causes of deviations in research findings are identified and compelling gaps in our knowledge with regards to the influence of partici pant gender, age and contextual factors are high lighted and discussed in relation to the broader literature. Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 105 publications
(132 reference statements)
4
21
1
Order By: Relevance
“…For example, Monk and Heim (2013) found participants to self-report higher levels of typical alcohol consumption when tested in a bar, opposed to lecture context. Furthermore, perceived norms are suggested to be context dependent, whereby alcohol-related environments will trigger normative beliefs associated with alcohol (Lo Monaco et al, 2011;Monk & Heim, 2014b). Along this line of thought, current findings suggest that injunctive norms regarding alcohol and engagement in risky behaviour may be more dominant in the alcohol-related environment, which may influence response of risk-taking questions on the RT-18.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…For example, Monk and Heim (2013) found participants to self-report higher levels of typical alcohol consumption when tested in a bar, opposed to lecture context. Furthermore, perceived norms are suggested to be context dependent, whereby alcohol-related environments will trigger normative beliefs associated with alcohol (Lo Monaco et al, 2011;Monk & Heim, 2014b). Along this line of thought, current findings suggest that injunctive norms regarding alcohol and engagement in risky behaviour may be more dominant in the alcohol-related environment, which may influence response of risk-taking questions on the RT-18.…”
Section: Discussionmentioning
confidence: 78%
“…To this end, laboratory and field work find opposing effects of alcohol consumption on risky behaviour. These inconsistencies may be a consequence of the environment and contextual difference between these studies, which have previously been suggested to impact alcohol-related cognitions (Monk & Heim, 2013a, 2013b, 2014b). …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, students often overestimate the actual drinking norms in these networks [9][10][11], which often encourage them to drink more alcohol than they would otherwise do [9,10]. Male students usually have higher misperceptions of existing drinking norms than female students [12] and these misperceptions generally refer to same-sex students [13,14].…”
Section: Introductionmentioning
confidence: 99%